Investigating The Impact Of Canopy Architecture On The Radiation Use Efficiency And Yield Of Sugar Beet - Tillier, Lucy (2023)
Current sugar beet varieties vary widely in their canopy architecture; some have a distinctively prostrate canopy angle whilst others are much more upright. Radiation use efficiency (RUE) is the amount of biomass accumulated per unit of light intercepted by the crop. In crops such as rice and wheat, where canopy architecture has been quantified, canopy angle has been shown to significantly influence light interception and RUE. This project quantifies canopy architecture and assesses its effect on RUE and yield of sugar beet.